PULMONARY ARTERIOVENOUS MALFORMATION TREATED BY LOBECTOMY - Yuksel, Mustafa; Ozyurtkan, Mehmet Oguzhan; Topaloglu, Nurhayat; Lacin, Tunc (Marmara Univ, Fac Medicine, 2005)
Pulmonary arteriovenous malformation (PAVM) is an abnormal communication between pulmonary arteries and pulmonary veins. These lesions are quite uncommon; they are an important part of the differential diagnosis of common pulmonary problems such as hypoxemia and pulmonary nodules. PAVM was observed in a 32-year-old woman who had the classical triad of cyanosis, polycythemia, and clubbing of the fingers and toes. She had also a brain abscess treated by drainage 10 years ago. Pulmonary angiography revealed two PAVMs located in the left upper lobe. She was treated by lobectomy.
Keywords: Arteriovenous malformations; Angiography; Clubbing; Polycythemia; Lobectomy